Simplifying
-6(11 + -2x) = 8(2x + -5) + -38
(11 * -6 + -2x * -6) = 8(2x + -5) + -38
(-66 + 12x) = 8(2x + -5) + -38
Reorder the terms:
-66 + 12x = 8(-5 + 2x) + -38
-66 + 12x = (-5 * 8 + 2x * 8) + -38
-66 + 12x = (-40 + 16x) + -38
Reorder the terms:
-66 + 12x = -40 + -38 + 16x
Combine like terms: -40 + -38 = -78
-66 + 12x = -78 + 16x
Solving
-66 + 12x = -78 + 16x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-16x' to each side of the equation.
-66 + 12x + -16x = -78 + 16x + -16x
Combine like terms: 12x + -16x = -4x
-66 + -4x = -78 + 16x + -16x
Combine like terms: 16x + -16x = 0
-66 + -4x = -78 + 0
-66 + -4x = -78
Add '66' to each side of the equation.
-66 + 66 + -4x = -78 + 66
Combine like terms: -66 + 66 = 0
0 + -4x = -78 + 66
-4x = -78 + 66
Combine like terms: -78 + 66 = -12
-4x = -12
Divide each side by '-4'.
x = 3
Simplifying
x = 3
2007-01-02 03:49:37
·
answer #1
·
answered by SHIBZ 2
·
1⤊
0⤋
-6(11 - 2x) = 8(2x - 5) - 38
- 66 + 12x = 16x - 40 - 38
- 66 + 12x = 16x - 78
- 66 + 12x - 12x = 16x - 78 - 12x
- 66 = 4x - 78
- 66 + 78 = 4x - 78 + 78
12 = 4x
12 / 4 = 4x / 4
3 = x
The answer is x = 3
INsert the x value into the equation
- - - - - - - - - - - - - - - - - - - - - - -
Check
- 6(11 - 2x = 8(2x - 5) - 38
- 6[ 11 - 2(3)] = 8[2(3) - 5] - 38
- 6 [ 11 - 6] = 8 [6 - 5] - 38
- 6[5] = 8 [1] - 38
- 30 = 8 - 38
- 30 = - 30
- - - - - - - - - s-
2007-01-02 05:33:11
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
Use distributive property:
-66+12x=16x-40-38
Combine like terms:
-66+12x=16x-78
Subtract 16x from both sides:
-66-4x=-78
Add 66 from both sides:
-4x=-12
Divide -3 from both sides:
x=3
Check:
-6(11-2(3))=8(2(3)-5)-38
-6(11-6)=8(6-5)-38
-6(5)=8(1)-38
-30=8-38
-30=-30
2007-01-02 03:53:19
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x=3
2007-01-02 03:53:38
·
answer #4
·
answered by araamdude 1
·
0⤊
0⤋
...
-6(11 - 2x) = 8(2x - 5) - 38
-66 + 12x = 16x - 40 - 38
12x - 16x = -78 + 66
-4x = -12
x = 3
...
2007-01-02 03:49:26
·
answer #5
·
answered by Jon 3
·
1⤊
0⤋
enable's simplify each thing. :) enable's first open the brackets and simplify. So, we've, 2x = 5 + 12x - 15 = -10 + 12x word: purely "3" is expanded to "(4x-5)" and not "5+3". including "10" to the two the aspects, we've, 2x + 10 = 12x Subtracting "2x" from the two the aspects, we've, 10 = 10x Dividing "10" by technique of the two the aspects, we've, a million = x it fairly is the comparable as x = a million wish that helped :)
2016-12-15 13:42:45
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
distribute
-66+12x=16x-40-38
combine like terms
-66+12x=16x-78
isolate the variable by adding 78 to both sides and subtracting 12x from both sides
12=4x
divide
3=x
2007-01-02 03:50:28
·
answer #7
·
answered by christopher_az 2
·
1⤊
0⤋
Distribute
-66+12x = 16x - 40 - 38
Subtract
-66 + 12x = 16x - 78
Place Like terms on the same sides
-66 + 12x = 16x - 78
- 12x - 12x
---------------------------
-66 = 4x - 78
+78 +78
--------------------------
12 = 4x
Divide by 4
x = 3
2007-01-02 04:47:15
·
answer #8
·
answered by krissyc39 2
·
0⤊
0⤋
-66+12x=16x-40-38
-66+12x=16x-78
/+78/ -66+12x=16x-78 /+78/
12+12x=16x
12+12x /-12x/ = 16x /-12x/
12 = 4x
3=x
2007-01-02 03:51:42
·
answer #9
·
answered by TeknoZX 1
·
1⤊
0⤋
Don't you need to solve this? How are going to learn how to do it if someone else does it?
2007-01-02 03:53:44
·
answer #10
·
answered by mel 3
·
0⤊
0⤋